Clinical Symptoms and Treatment Outcomes of COVID-19 Patients with Stroke - Daud, Oskar Yuda; Sinurat, Robert (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: COVID-19 patients who come to the emergency room often suffer from stroke. This study aimed to examine clinical symptoms and treatment outcomes of COVID-19 patients with stroke.Methods: This study was a retrospective study using secondary data from medical records of COVID-19 patients with stroke, hospitalized at the Universitas Kristen Indonesia Hospital, Jakarta, Indonesia for the period 2020–2022. Patients with PCR test positive for COVID-19 who had clinical symptoms of stroke, confirmed by CT scan showing brain ischemic or hemorrhage were included. Data on gender, age, Glasgow coma scale (GCS), subtype of stroke, severity of COVID-19, and outcome were recorded and analyzed using paired t-test and the Spearman correlation.Results: Of the 49 patients included, 91.8% were over 45 years old and suffered from severe COVID-19. Men were slightly more (51.1%) than women and 93.9% of patients suffered from ischemic stroke. The GCS scores of 46.9% of patients decreased significantly during hospitalization (p=0.02). Most of patients (65.3%) had used non-rebreathing mask (NRM), 10.2% ventilators, and others used nasal cannulas. As many as 46.9% of patients died, 44.9% recovered with neurological deficits, and only 8.2% recovered completely. Interestingly, oxygen delivery devices were significantly correlated with outcome (p=0.00). Patients receiving the antiviral favipiravir had better outcomes compared with those taking remdesivir (p=0.021).Conclusion: The mortality rate for stroke patients with severe COVID-19 is high, and the outcome of patients using NRM or ventilator is worse than patients using nasal cannulas. The antiviral Favipiravir has better outcomes for stroke patients with severe COVID-19.